2009
DOI: 10.1080/08916930902787716
|View full text |Cite
|
Sign up to set email alerts
|

Infection and thyroid autoimmunity: A seroepidemiologic study of TPOaAb

Abstract: Infectious agents have been implicated as triggers of autoimmunity. Prospective epidemiologic studies of infection with specific pathogens and the subsequent elevation of specific autoantibodies are difficult and costly to conduct. As a result, a solid body of evidence regarding this theoretically intriguing connection remains to be accrued. We studied term sera from 1807 pregnancies in 1591 women for whom IgG status for cytomegalovirus, Epstein-Barr virus, herpes simplex virus type 1, herpes simplex virus typ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
24
2

Year Published

2010
2010
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(29 citation statements)
references
References 51 publications
3
24
2
Order By: Relevance
“…This is well supported by the observation that ATxA from healthy individuals cross-react with malignant cervical tissue antigens [34]. Second, an association between ATxAeIgG antibodies and antithyorid antibodies (TPOAb) was observed in sera from 1591 pregnant women [21]. Thus supporting, along with our data on AITD, the hypothesis that Toxoplasma can initiate a pathogenic process that may eventually result in clinically overt autoimmunity.…”
Section: Discussionsupporting
confidence: 78%
See 2 more Smart Citations
“…This is well supported by the observation that ATxA from healthy individuals cross-react with malignant cervical tissue antigens [34]. Second, an association between ATxAeIgG antibodies and antithyorid antibodies (TPOAb) was observed in sera from 1591 pregnant women [21]. Thus supporting, along with our data on AITD, the hypothesis that Toxoplasma can initiate a pathogenic process that may eventually result in clinically overt autoimmunity.…”
Section: Discussionsupporting
confidence: 78%
“…The present data support this view of APS pathogenesis by demonstrating an ATxA association with aPL antibodies and the anti-phospholipids syndrome. Third, we may hypothesize that T. gondii infection induces a bystander effect via activation of toll-like receptors (TLR) [21], as previously demonstrated for multiple TLR [35], and may thus lead to the expansion of autoantibodies under aberrant conditions (e.g., excessive and/or chronic TLR activation) [21,36].…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…This report is the first to demonstrate the link between EBV infection and Graves' disease. On the other hand, it has been suggested that no differences were observed between patients with Graves' disease and controls in the prevalence of IgG antibodies against EBV (25,26). The role of EBV infection in the pathogenesis of Graves' disease has is not been fully elucidated.…”
Section: Discussionmentioning
confidence: 96%
“…A possible role of microchimerism in the pathogenesis of some autoimmune diseases has been suggested because microchimeric cells may differentiate into many lineages in various tissues finally inducing diverse pathophysiologic processes during the host lifetime [276] (Table 4). For example, proliferation of these cells in maternal tissue environment may be at least in part responsible for development of autoimmune thyroid diseases because of a significant prevalence of anti-IgG T. gondii antibodies present in those individuals [25,277,278], as well as papillary thyroid cancer induction [279]. Fetal microchimerism may take place during pregnancy starting from the 4 th to 6 th week of gestation [280].…”
Section: Diabeticsmentioning
confidence: 99%